The Influence of Corruption and Language on the Protrade Effect of Immigrants: Evidence from the American States - Dunlevy, James A. (The Review of Economics and Statistics, 2006)
The protrade effect of immigrants on the bilateral export performance of the 50 American states and the District of Columbia with respect to 87 foreign countries is studied. This effect, which posits that a greater number of immigrants in a host location leads to increased trade between the host and the immigrants' origin country, has been supported in a number of studies. Here, we extend this approach and find that the immigrant effect is greater when the origin country's political system is more corrupt and less important when Spanish or English is the language of the origin country. State-level export data averaged over the 1990–1992 period are used.